Paternal Exposure to Methylphenidate Induces Poor‐Quality Blastocyst and Epigenetic Changes - Gomes, Ana Clara da Costa Nunes; Pagliari, Laura Eduarda S. C.; Stumpp, Taiza; Vendramini, Vanessa (Molecular reproduction and development, 2025)
ABSTRACT Epigenetic changes caused by methylphenidate hydrochloride on paternal inheritance have been suggested in fish, yet a subject to be determined in mammals. In rats, we showed increased sperm DNA fragmentation and reduced embryonic viability. In the present report, male Wistar rats (n = 21) were divided into two groups: control and methylphenidate. The control group received 1 mL/kg of distilled water, while the methylphenidate group received 5 mg/kg by gavage from 38 to 68 days of age on a single daily dose. After this period, there was an interval before exposed rats started a mating schedule with untreated/normally cycling females. Morphological quality and key epigenetic marks in the blastocysts were assessed. Immunocytochemistry was performed in fresh blastocysts to quantify the trimethylated histones H3K4, H3K9, and H4K20. Treatment with methylphenidate reduced the mean quality of blastocysts by 43.57% (p = 0.02), as well as increased those classified as “poor” by more than 150% (p < 0.001). Epigenetic marks were also altered, with an increase in the intensity of H3K9me3 (p = 0.01), a reduction of H4K20me3 (p = 0.05) and a nonsignificant increase of H3K4me3 (p = 0.34). The results suggest that the decline in blastocyst quality is highly associated with subchronic use of this psychostimulant by adolescent males. This is the first report showing the risks posed by methylphenidate to the epigenetic signature of a mammalian blastocyst following paternal exposure.